Can Short Anogenital Distance Cause Chronic Prostatitis? Anogenital distance in chronic prostatitis - Verit, Ayhan; Verit, Fatma Ferda (Urology Journal, 2021)
Chronic prostatitis/Chronic pelvic pain syndromes (CP/CPPS) are a widespread pathology with unknown etiology without a proved treatment algorithm. Neurologic, endocrine and immune systems, and oxidative stress, infections are ranked in the physiopathology. Anogenital distance (AGD) as a marker for the degree of antenatal exposure of androgens that link to some disorders of androgen-sensitive tissues especially of urogenital system. In this study, we aimed a construct a hypothesis that improper development of perineum and pelvic bottom due to the insufficient embryologic androgen exposure, which can be detected by reduced AGD, can form histologic/clinic CP in adulthood through the physical forces that resulted in stretched prostate via chronic hypoxia induced oxidative stress and failed immune mechanisms. AGD, unlike the previous published ones, suggested as a real physical scale to detect narrowed pelvic bottom other than an endocrine related biomarker.